Linguistic Profile Test – Normative Data for Children in Grades VI to X (11+ Years – 15+ years) - Suchithra M.G.; Prathibha Karanth (Journal of All India Institute of Speech and Hearing, 2007)
In view of the near total absence of literature on language acquisition in older children, in the India context, this study focused on the collection of normative data for older school going children from Grades VI to X on the Linguistics Profile Test (LPT). One hundred and fifty children ranging in age from 11+ years to 15+ years were the subjects in the current study. There were 30 subjects in each age group. The mean and SD of each of the three sections (Phonology, Syntax and Semantics) of LPT was obtained. It was found that the mean scores gradually increased over years. The findings of this study are on line with the earlier studies on Hindi Speaking adults as well as children of same age group. The norms thus established may be used for evaluation and identification of delayed language acquisition in older children in Kannada.